Increasing Learning Outcomes and Critical Thinking Skills Through Project Based Learning Strategy Integrated with Local Wisdom ’Dangke’ Approach in Science Learning - Muh Idham Haliq; Nur Hikmah; M Yunus Sudirman (Edumaspul: Jurnal Pendidikan, 2023)
The research aims to determine the effect of the Project Based Learning (PjBL) strategy integrated with the local cultural wisdom of making dangke in improving learning outcomes and critical thinking skills of elementary school students in science material. This type of research is experimental research carried out at SDN 122 Pangbuluran in 2023. The subjects of this research are fourth grade elementary school students, who are divided into an experimental group and a control group. The data analysis techniques used are: descriptive data analysis in the form of: mean, data range, class interval, class length, percentage, variance and standard deviation; and inferential statistical data analysis techniques in the form of: normality test, homogeneity test, and hypothesis test. The instruments used are multiple choice questions to measure student learning outcomes and essay questions that have been validated and declared reliable as test instruments. The results of data analysis obtained hypothesis testing: tcount learning outcomes of 10.2 > ttable, until H0 rejected, while tcountcritical thinking skills of 9.9 > ttable, until H0 rejected. It can be concluded that there is an influence of the Project Based Learning (PjBL) strategy integrated with local cultural wisdom in making dangke in improving learning outcomes and critical thinking skills of elementary school students in science material.